Academic Habitus and Institutional Change: Comparing Two Generations of German Scholars - Hildegard Matthies; Marc Torka (Minerva, 2019)
Since the 1980s scholars have been increasingly confronted with expectations to orient themselves toward societal and economic priorities. This normative demand for societal responsiveness is inscribed in discourses aimed at increasing the usefulness, competitiveness, and control of academia. New performance criteria, funding conditions, and organizational forms are central drivers of this debate – thereby, they change the conditions in which scholars conduct research and advance their careers. However, little is known so far about the impact these institutional changes have on the habitus of academics. This article analyzes how stable and consistent habitus formations among academics turn out to be in the course of institutional changes. We compare the habitus formations of two generations of German scholars before and after institutional changes gained pace in Germany. Three distinct habitus formations can be identified, which we refer to as “self-fulfilling,” “self-surpassing,” and “self-asserting.” These habitus formations hold across the two generations, but the lines between them become blurry in the new generation.
Keywords: 300; academic habitus; habitus transformation; academic careers; institutional change